The Implementation of f(x) = 3(x 3 − x 2 − x) + 2 as CSPRNG Chaos-Based Random Number Generator - Yopeng, Maria Rosalina; Wowor, Alz Danny (Indonesian Journal on Computing (Indo-JC), 2021)
This research implemented the cubic function f(x) = 3(x^3 − x^2 − x) + 2 using a FixedPoint Iteration to produce several iteration functions that can be used as random number generator. The test results obtain six iteration functions, and based on graphic visualizationwith Scatter plot and randomness test with mono bit test, bit block, and run test, the results only obtain two iteration functions namely x2 − 1 + 2/(3x) and f(x) = 1 + 1/x − 2/(3x^2)which can produce CSPRNG Chaos-based random number. Encryption testing shows that both functions can generate keys that make plaintext and ciphertext statistically unrelated, so the f(x) = 1 + 1/x − 2/(3x^2) function can be used as a CSPNRG chaos-based random number generator function.